This is just my face : try not to stare - Sidibe, Gabourey (Houghton Mifflin Harcourt, 2017)
The star of "Precious" and "Empire" shares details about her childhood with a polygamous father in Harlem, her gifted mother who supported them by singing in the subway, and her own unconventional rise to fame.